2011
DOI: 10.1111/j.1547-5069.2010.01374.x
|View full text |Cite
|
Sign up to set email alerts
|

Translating the Insomnia Severity Index Into Arabic

Abstract: Preliminary psychometric estimates show that the translated ISI is reliable and valid in this community-dwelling Arabic sample. The translated ISI allows for Arabic researchers to screen for insomnia and plan for future intervention studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 16 publications
5
94
0
1
Order By: Relevance
“…The item-total correlations ranged from 0.65 to 0.84, thus also exceeding the usual accepted value of 0.30 41. The value of Cronbach's alpha was higher than 0.74, which was first established for examining the validation of clinical tests,16 and similar to those achieved by the Arabic27 and Hindi25 versions of the ISI (0.92 and 0.91, respectively). However, the item-total correlations of the current research were more stable than those of the Arabic27 and Hindi25 versions (0.49-0.92 and 0.56-0.87, respectively).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The item-total correlations ranged from 0.65 to 0.84, thus also exceeding the usual accepted value of 0.30 41. The value of Cronbach's alpha was higher than 0.74, which was first established for examining the validation of clinical tests,16 and similar to those achieved by the Arabic27 and Hindi25 versions of the ISI (0.92 and 0.91, respectively). However, the item-total correlations of the current research were more stable than those of the Arabic27 and Hindi25 versions (0.49-0.92 and 0.56-0.87, respectively).…”
Section: Discussionmentioning
confidence: 79%
“…The PSQI is a widely used measure of sleep quality32 and has been used in previous studies as a convergent measure with ISI in other language versions 24,26,27. PSG was used as the primary diagnosis tool for other sleep disorders, and as a complementary instrument for the evaluation of insomnia, although it is not indicated for the routine evaluation of this condition 33,34…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we used the ISI to assess the patient's perception of his or her insomnia and the severity of both nighttime and daytime components of insomnia since it has been subject to several validation studies, and its psychometric qualities are highlighted by many publications [14][15][16][17][18][19]. It is available in several languages and is increasingly used as a metric in clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a previous literature participants, scoring 10 or more were considered to be insomniacs 16 . Prior research utilized the Arabic version of ISI, which was showed to be reliable with an internal consistency of 0.84 17 . In the current study, ISI was showed to have good reliability with a Cronbach's alpha score of 0.89.…”
Section: Study Instrumentsmentioning
confidence: 99%